The Islamization of Science in the Era of Society 5.0: Study of the Thought of Ismail Raji Al-Faruqi and Syed Naquib Al-Attas - Septian Aristya; Rachmat Soe’oed; Khojir (STAIN MAJENE, 2022)
Science is one of the important elements that must be possessed by humans, human development is also never separated from science. The development of science, especially from the west, also requires a filter so that secular values ​​that are not in accordance with Islam can be prevented. The importance of Islamization of science is a main concept that can be a vaccine to prevent negative values ​​that accompany science and can also be a vitamin to increase the spirit of Muslims to always try to develop science.Several Muslim figures who initiated the concept of Islamization of Science, including Syed Naquib Al-Attas and Ismail Raji Al-Faruqi, the two Muslim figures considered the Islamization of science as a solution to the problem of the current dichotomy of science. Especially where we have entered the era of Society 5.0 where the development of technology and science has become a necessity without leaving important human aspects as the main element in that era.As for the use of this research method, it uses a pure library research method with a descriptive analytical approach, namely describing and critically interpreting the meaning of the discussion process so as to make a new idea in the development of science. The purpose of this study is to find a correlation between the Islamization of science in the era of society 5.0 and the study of the concepts offered by Ismail Raji al-Faruqi and Syed Naquib al-Attas. And from the results of this study, it was found that there was a correlation between the Islamization of science in the era of Society 5.0, this was seen in the strengthening of humans as the center of civilization so that the concept of Islamization became a solution to the gap and strengthened human character in particular.